2015
DOI: 10.22215/timreview/952
|View full text |Cite
|
Sign up to set email alerts
|

Contextuality and Co-Creation Matter: A Qualitative Case Study Comparison of Living Lab Concepts in Urban Research

Abstract: IntroductionLiving labs have become an established tool for testing and developing new products or services with users in real-life environments (see Leminen et al., 2012;Veeckman et al., 2013). They were also introduced into urban research agendas by the Finnish European Union Presidency in 2006. Since then, research programmes have been using living labs as a methodological tool to connect research to public and private stakeholders with citizens in order to co-create and co-design products and services to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 12 publications
0
14
0
1
Order By: Relevance
“…Learning and experimenting (McCormick, 2016;Pallot & Pawar, 2012;Schaub, 2016;Vincent, 2016) refers to the production and exchange of knowledge among participants (ASC, 2016;Bijsterveldt, 2016;Friedrich et al, 2013;Heijden, 2016;McCormick, 2016;Pallot & Pawar, 2012). Thus, the aim is not only to learn from the experiences from the particular lab environment, but also to replicate the innovation elsewhere, in real life, or to further future innovation (ASC, 2016;Bijsterveldt, 2016;Franz et al, 2015;Juujärvi & Lund, 2016). It is this emphasis on formalized knowledge production -lessons that are formulated and that can be disseminated -that sets living labs apart from other policy experiments and niches of innovation (Evans & Karvonen, 2014).…”
Section: Aimmentioning
confidence: 99%
See 2 more Smart Citations
“…Learning and experimenting (McCormick, 2016;Pallot & Pawar, 2012;Schaub, 2016;Vincent, 2016) refers to the production and exchange of knowledge among participants (ASC, 2016;Bijsterveldt, 2016;Friedrich et al, 2013;Heijden, 2016;McCormick, 2016;Pallot & Pawar, 2012). Thus, the aim is not only to learn from the experiences from the particular lab environment, but also to replicate the innovation elsewhere, in real life, or to further future innovation (ASC, 2016;Bijsterveldt, 2016;Franz et al, 2015;Juujärvi & Lund, 2016). It is this emphasis on formalized knowledge production -lessons that are formulated and that can be disseminated -that sets living labs apart from other policy experiments and niches of innovation (Evans & Karvonen, 2014).…”
Section: Aimmentioning
confidence: 99%
“…Living labs should comprise the development of a product, which can be all sorts of artifacts, including process innovations, and not only, for example, testing or implementation (Budweg et al, 2011;Coenen et al, 2014;Feurstein et al, 2008;Gray et al, 2014;Leminen, 2015;Schaffers et al, 2007;Tang & Hämäläinen, 2012). A key element in this development process is co-creation (Bijsterveldt, 2016;ENoLL, 2016;Feurstein et al, 2008;Franz et al, 2015;Gómez-Barroso et al, 2009;Heijden, 2016;Schaub, 2016). The essence of a living lab is that the solution is sought together with the user, rather than just applying a fixed solution and involving the user only for testing.…”
Section: Aimmentioning
confidence: 99%
See 1 more Smart Citation
“…Other examples highlight issues regarding end-user participation. In a qualitative case study comparison, Franz et al (2015) demonstrated a deficit in the traditional co-creation methodology, as the project team was responsible for most decisions about defining the problem, as well as selecting stakeholders and methods. Hyysalo and Hakkarainen (2014) show that collaboration between designers and users is often a hard and frustrating process.…”
Section: Discussionmentioning
confidence: 99%
“…Da la oportunidad de integrar ideas y prototipos de productos complejos dentro de un entorno que se parece mucho al contexto del producto en la vida real". Franz, Tausz & Thiel (2015): Contextuality and Co-creation Matter: A qualitative case study comparison on Living Lab concepts in urban research "Aunque los proyectos y enfoques de los Laboratorios Vivos difieren ampliamente, los beneficios radican en la integración del usuario y el uso de los resultados para desarrollar productos y servicios basados en las necesidades que se pueden implementar en los entornos de vida de los ciudadanos" Bergvall-Kåreborn, Eriksson, & Ståhlbröst (2015): Places and Spaces within Living Labs "Un Laboratorio Vivo es un entorno de innovación centrado en el usuario basado en la práctica e investigación diaria, con un enfoque que facilita la influencia del usuario en procesos de innovación abiertos y distribuidos, involucrando a todos los socios relevantes en contextos de la vida real, con el objetivo de crear valores sostenibles". Rits, Schuurman & Ballon (2015): Exploring the Benefits of Integrating Business Model Research within Living Lab Projects "La definición de Laboratorio Vivo sigue siendo una discusión no resuelta y en gran parte semántica.…”
Section: Shuurman De Marez and Ballonunclassified